Regulation of human vascular redox state in obesity and insulin resistance - Akoumianakis, I (2019)
Insulin resistance (IR) and dysfunctional adipose tissue (AT) secretome are believed to mediate the mechanistic links between metabolic and vascular disease. However, the mechanistic details of the interactions between vascular IR, AT-derived products and vascular disease phenotypes in humans are poorly understood. In the first part of my thesis, I attempted to characterise downstream vascular insulin signalling in patients with atherosclerosis and how this could be modified to regulate vascular insulin sensitivity. In the second part of this work, I explored the role of AT-derived Wnt5a (a novel, AT-secreted glycoprotein with inadequately characterised vascular roles) as a link between metabolic and vascular disease via direct regulation of vascular redox state and endothelial function. For these purposes, I used the Oxford cohort for Fat, Vessels and Fat (OxHVF), a uniquely phenotyped cohort of >1,000 patients undergoing cardiac surgery) to perform observational association studies and functional ex vivo bioassays on intact vascular tissues, which were also complemented by appropriate in vitro mechanistic experiments. I firstly demonstrated that vascular IR is a universal feature of human atherosclerosis irrespectively of the presence of systemic IR, characterised by disproportionally increased Erk1&2 activation as opposed to Akt activation in response to insulin. This can be reversed by pre-treatment with a dipeptidyl peptidase 4 (DD4) inhibitor, thus identifying vascular insulin-sensitising roles for this class of drugs. In the second part of my thesis, I revealed that systemic Wnt5a bioavailability is increased in obesity, diabetes and vascular disease, while Wnt5a (partially originating from AT) can induce vascular NADPH-oxidase activation via a novel USP17 interaction through paracrine and endocrine ways, also accompanied by endothelial dysfunction, eNOS uncoupling and redox-sensitive VSMC phenotype changes. My findings provide novel links between obesity, insulin resistance and vascular disease mechanisms and pose significant therapeutic implications.